Bank Syariah Indonesia Dispute? (Analysis of Decision No. 220/Pdt.G/2023/PA.PSP) - Lubis, Rahmat Husein (Sharia Faculty Islamic Economic Law Study Department, 2025)
The purpose of this study is to analyze how to resolve sharia economic disputes, especially in Indonesian Sharia Banks with the Murabahah Agreement at the Padangsidimpuan Religious Court in decision No. 220/Pdt.G/2023/PA.Psp. The nature of this research uses a qualitative descriptive method with a case study method. The location of this research is the Padangsidimpuan Religious Court. The results of the study found that BSI's dispute over the Mudharabah contract contract that had been carried out between the Plaintiff and Defendant I had fulfilled the principles and conditions of the contract as described in articles 22, to 25 of the Compilation of Sharia Economic Law which was resolved at the Padangsidimpuan Religious Court starting with the object of the murabahah contract dispute between the Plaintiff and Defendant I so that Defendant I submitted an application to grant the object to KPKN. Between the plaintiff and defendant I it has been done and has been running and the plaintiff has benefited from the contract, so the exception is challenged II and rejected in its entirety. Then the defendant was charged a case fee of Rp. 3,270,000.